RECLAMATION OF EX-PETI AGRICULTURAL LAND IN MERANGIN DISTRICT (CASE STUDY IN PANGKALAN JAMBU DISTRICT MERANGIN REGENCY, JAMBI PROVINCE IN 2020) - Arislan Arislan; M. Syukurman; Mardalena Mardalena (Dinasti Publisher, 2021)
Unlicensed gold mining (PETI) is rife in the community, especially entrepreneurs / capital owners since the last ten years in Merangin Regency. Lack of awareness of negative impacts is a problem that needs serious attention from the government. There are miners who come from outside and from the community itself. Even though PETI is difficult to overcome, many of the people who own the land have processed it to be planted with rice again. In other places or areas in Indonesia, many ex-PETI lands cannot be planted with rice anymore because they have already contaminated with mercury. Due to the fact that many ex-PETI lands have been re-processed into paddy fields in Merangin Regency, a research was conducted which took place in Pangkalan Jambu District. The reason for choosing Pangkalan Jambu sub-district as the research location is because in this sub-district the largest area of ??land in Merangin Regency is being mined by the community. The research was conducted with a case study qualitative approach with data collection techniques, observation, interviews and documentation. The purpose of this study was to examine the processing of ex-PETI rice fields into reclamation. The results of the study concluded that the reclamation activity was carried out after several landowners tried to plant rice on the ex-PETI land which was successful and did not encounter any significant obstacles. Starting from here, other residents did the same thing and it turns out that it continues to grow until now. As the reason why rice plants can thrive, it turns out that in this place the miners do not use mercury when mining. Previously, the area of productive rice fields was 1202 ha and now, of the eight villages, the number of rice fields that have been reproducing (reclaimed) is 139 ha. There are 804 ha of rice fields damaged by PETI and there are 259 ha of land that are not damaged but have not yet operated or have not recovered and need to be reclaimed again.